PENGARUH KEPUASAN KERJA, KOMPENSASI NON FINANSIAL DAN LINGKUNGAN KERJA FISIK TERHADAP SEMANGAT KERJA KARYAWAN PADA KANTOR PT. PERKEBUNAN NUSANTARA V KEBUN LUBUK DALAM KABUPATEN SIAK - Fikrian Hamdila Pratama; Dewita Suryanti Ningsih; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Perkebunan Nusantara V Kebun Lubuk Dalam Kabupaten Of Siak order to determine the effect of variable Job Satisfaction, non Financial Compensation and Work Environment Physical, simultaneously on Spirit of employees. This study uses primary data obtained from interviews and giving questionnaires to all employees of PT. Perkebunan Nusantara V Kebun Lubuk Dalam Kabupaten Of Siak. Secondary data were obtained relating to the object and the organizational structure of the population in this study were all employees that totaled 49 people and sampled. The analytical method used in this research is multiple linear regression method. From the testing that has been done, simultaneous regression test (Test-F) shows that job satisfaction variable, non-Financial Compensation and Working Environment Physical simultaneously significant effect on Spirit Employees. From the results of the partial test (t-test) showed that job satisfaction variable, non-Financial Compensation and Working Environment Physical significant effect on spirit employees. The result of the calculation of the coefficient of determination (R2) amounted to 0,656, which means, variable Job Satisfaction, non Financial Compensation and Working Environment Physical against spirit employees, while the rest influenced by other variables not examined in this study.Keywords: Job Satisfaction, Compensation Non Financial, Physical Work Environment and spirit employees